The Relationship between the School Breakfast Program and Food Insecurity. Issue 3 (27th September 2017) - Fletcher, Jason M.; Frisvold, David E.
Abstract : Food insecurity rates have risen significantly in the United States, beginning with the recent recession, and remained high. The implications of these high rates are severe in that food insecurity has been associated with a wide range of health, behavioral, social, and cognitive difficulties. This article examines the relationship between the School Breakfast Program (SBP) and food insecurity outcomes. The SBP has the potential to reduce food insecurity because of the direct provision of breakfast to students and the implied income transfer to households. We use state‐level cutoffs tied to school‐level poverty rates that mandate the provision of the SBP to compare the food security outcomes of students in similar schools, but with different requirements to provide breakfast. Our estimates suggest that state policies requiring schools to offer the SBP have reduced food insecurity for young children.